SOA Command and Control taking SOA to the next level. - Foody, Dan
One of the ongoing challenges for business today is finding ways to do more with less. Companies are under relentless pressure to deliver products and services to market faster, better and cheaper than ever before. Investments in information technology are expected to drive the business forward, not only in terms of gaining efficiencies and increasing responsiveness, but in creating new top-line opportunities.